STRATEGI MANAJEMEN REVENUE GUNA UNTUK MENINGKATKAN PENDAPATAN DI FIFTEENTH CAFÉ SURABAYA - Baskoro, Farhan Maulana; Herlina, Herlina (Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The decline in the number of visitors is caused by the emergence of many competitors and business places today which make business owners worry that their business will fade away until they eventually go bankrupt. One of the factors causing a decrease in revenue at Fifteenth Café is the large number of empty seats during the cold hours. On the other hand, when it's hot, it's difficult for customers to get a seat. This requires a strategy to increase cafe revenue. Revenue management is a method used to sell the right inventory to the right customers at the right time at the right price. Revenue Management is carried out using 5-steps where in this study it was only carried out up to the third step, namely establishing a baseline, analyzing problems, and creating a revenue management strategy. The problems experienced by Fifteenth Cafe were caused by reservation policies, difficulty attracting visitors, inefficient table-chair composition, and delays in the service system process. From these problems, several strategic recommendations were obtained, such as hold tables on reservation policies, changes in table-chair composition and service process improvements